Removal of Lead and Iron in Leachate Wastewater of The TPST Piyungan by Activated Natural Zeolite - Totok Eka Suharto; Siti Salamah (Elkawnie: Journal of Islamic Science and Technology, 2023)
Abstract: Landfill generates a problem of soil and water pollution, with leachate wastewater contaminating heavy metals. Wastewater treatment with natural zeolite adsorbents can remove heavy metals from wastewater. We have analyzed the leachate wastewater in the last pond at the wastewater treatment plant at the TPST Piyungan contains lead (Pb) ions of 2.13 mg/L and iron (Fe) of 9.94 mg/L, greater than the maximum levels allowed for sanitary hygienic water. according to the regulations of the Minister of Health. The concentration of Pb and Fe metal ions in wastewater can be removed by activated local natural zeolite adsorbents. The adsorbent was prepared from local natural zeolite by activation with ammonium nitrate solution and calcined at 300 oC for 2 hours. Characterization by XRD, BET-adsorption analysis, and SEM showed that activation can increase natural zeolite's surface area and pore size without being followed by a change in the crystal structure. The leachate adsorption experiment was carried out by varying the weight percentage of activated natural zeolite adsorbent and adsorption time. The concentration of Pb and Fe ions in wastewater can be reduced by activated natural zeolite adsorbents. Adsorption with 10% weight of natural zeolite and an adsorption time of 60 minutes delivered the best results. Under these adsorption conditions, the concentration of Pb ions decreased by 38.50% and that of Fe decreased by 67.10%. The adsorption treatment with activated natural zeolite can significantly reduce the concentration of Pb and Fe metal ions in the waste leachate of TPST Piyungan.Abstrak: Tempat Pembuangan Sampah (TPS) menimbulkan masalah polusi air dan tanah dengan air limbah lindi yang mengandung logam-logam berat. Perlakuan dengan adsorben zeolit alam dapat mengurangi logam berat dalam air limbah. Analisis dengan AAS menunjukkan bahwa air limbah pada kolam terakhir instalasi pengolahan air limbah di TPST Piyungan mengandung ion logam timbal (Pb) 2,13 mg/L dan besi 9,90 mg/L. Kadar kedua logam berat ini melebihi ambang batas yang dibolehkan dalam air untuk sanitasi higin menurut regulasi Kementerian Kesehatan. Konsentrasi ion logam Pb dan Fe dapat dikurangi dengan adsorben zeolit alam lokal yang diaktivasi. Adsorben dibuat dengan aktivasi zeolit alam lokal dengan larutan ammonium nitrat dan dikalsinasi pada 300oC selama 2 jam. Hasil analisis adsorben dengan XRD, analisis adsorpsi BET, dan SEM menunjukkan bahwa aktivasi dapat menaikkan luas permukaan zeolit dan ukuran pori tanpa diikuti perubahan struktur kristal. Eksperimen adsorpsi limbah lindi dilakukan dengan variasi persentase berat adsorben zeolit alam dan waktu adsorpsi. Konsentrasi ion Pb dan Fe dalam limbah lindi dapat dikurangi dengan adsorben zeolit alam teraktivasi. Hasil terbaik diperoleh dengan penggunaan 10% berat adsorben zeolit dan waktu adsorpsi 60 menit. Pada kondisi ini konsentrasi ion Pb berkurang 38,50% dan Fe turun sebesar 67,10%. Perlakuan adsorpsi dengan zeolit alam teraktivasi dapat mengurangi secara signifikan konsentrasi ion logam Pb dan Fe dalam limbah lindi TPST Piyungan.